2010
DOI: 10.1080/10508422.2010.491767
|View full text |Cite
|
Sign up to set email alerts
|

Corrected Feedback: A Procedure to Enhance Recall of Informed Consent to Research Among Substance Abusing Offenders

Abstract: This study examined the efficacy of corrected feedback for improving consent recall throughout the course of an ongoing longitudinal study. Participants (N = 135) were randomly assigned to either a corrected feedback or a no-feedback control condition. Participants completed a consent quiz 2-weeks after consenting to the host study and at months 1, 2, and 3. The corrected feedback group received corrections to erroneous responses and the no-feedback control group did not. The feedback group displayed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…[32, 33] Given that longer-term retention of information is typically poor, this approach allows the investigator to assess understanding at the time decisions are actually made. These exercises are also useful in identifying problem areas and in directing investigator efforts towards targeted discussion.…”
Section: Discussionmentioning
confidence: 99%
“…[32, 33] Given that longer-term retention of information is typically poor, this approach allows the investigator to assess understanding at the time decisions are actually made. These exercises are also useful in identifying problem areas and in directing investigator efforts towards targeted discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have found cognitive variables (IQ, memory, attention) to be positively correlated with consent recall, 1,2,6,23 in statistical combination, these variables account for less than half of the variance. 24 This suggests that remedial strategies may address only part of the problem and that other factors may be involved.…”
mentioning
confidence: 90%
“…Participants are often unaware that they were participating in a research study, fail to recall study-related risks, are unable to describe randomization procedures or placebo interventions, and are unaware that they can withdraw from a study without negative consequences. 35 Research in a population of substance abusing offenders 6,7 revealed that participants failed to recall 60% of consent information just two weeks after their initial consent, calling into question whether participants can make informed decisions about their initial or continued involvement in research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be accomplished by using audio-visual tools, such as videos that clearly communicate the risks and benefits of participating in research (Dunn andJeste, 2001 andFureman et al, 1997). The validity of consent may also be increased by a consent process that assesses participants' understanding of the research study and the risks and benefits of participation, and corrects any misunderstandings (Festinger, Dugosh, Croft, Arabia, & Marlowe, 2010). More research is required on how best to obtain consent to research participation in substance abusing populations (Carter and Hall, 2008, Dunn and Jeste, 2001and Festinger et al, 2010.…”
Section: Studies Of Craving In Formerly Dependent Individualsmentioning
confidence: 99%